Energy for sustainable development demand, supply, conversion and management - Hasanuzzaman, Mirza; Rahim, Nasrudin Abd (Academic Press, 2020)
"Energy for Sustainable Development: Demand, Supply, Conversion and Management presents a comprehensive look at recent developments and provides guidance on energy demand, supply, analysis and forecasting of modern energy technologies for sustainable energy conversion. The book analyzes energy management techniques and the economic and environmental impact of energy usage and storage. Including modern theories and the latest technologies used in the conversion of energy for traditional fossil fuels and renewable energy sources, this book provides a valuable reference on recent innovations. Researchers, engineers and policymakers will find this book to be a comprehensive guide on modern theories and technologies for sustainable development"--